PERILAKU PROFESIONAL TENAGA KESEHATAN DAERAH PESISIR PADA PELAYANAN KESEHATAN PRIMER PUSKESMAS SUNGAI SEMBILAN KOTA DUMAI TAHUN 2014 - Dicky Pangestu Sandjaya; Dedi Afandi; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
One of important aspect to support optimal health care improvement is the availability of health worker who have professional conduct, especially in coastal region. It is due to the low level of public health in the most of the coastal region in Indonesia. Needs of the professional health workers in the coastal region are in the health care center as the first strata health care centers area that become advance in providing services. Exploration method with qualitative approaches was applied as the research design. Seven health care workers of Puskesmas Sungai Sembilan Dumai City were selected as responden by using snowball sampling method. Data were collected by using interview method recorded with an audio recorder. The result of this research showed that all the informants possess altruism, accountability, excellence, honor and integrity. duty and respect for other.Key word : professional behavior, health-care workers